Seroprevalence of Dengue infection in clinically suspected cases of dengue at tertiary care hospital in central India - P. Nikam, Archana; R. Bhise, Pramod; M. Deshmukh, Mukta (International Journal of Medical Research and Review, 2015)
Introduction: Dengue is one of the most serious mosquito borne viral infection of man affecting mainly tropical and subtropical countries and caused by four serotypes of dengue virus, namely DEN-1, DEN-2, DEN-3 and DEN-4 belonging to genus flavivirus and family flaviviridae. It spreads through the bite of infected Aedes mosquito. Dengue is potentially fatal viral infection that can culminate into dengue hemorrhagic fever (DHF) and dengue shock syndrome (DSS). The newer parameter NS1 antigen is detectable from day 1 of fever both in primary and secondary infections. Materials and Methods: Blood samples from clinically suspected cases of dengue tested immediately for qualitative detection of NS1 Ag, IgM and IgG antibodies by rapid solid phase immunochromatography test (ICT). Results: Out of 1090 samples tested, a total of 354 samples were tested positive for either one or more of the three markers i.e. NS1 Ag, IgM and IgG antibody tested. Of the 354 serum samples, 182 (51.41%) patients were positive for NS1 Ag only, 29 (8.19%) positive for IgM only, while 54 (15.25%) were positive for IgG only. More than one marker was detected in the remaining 89 (25.14%) samples. Primary dengue was detected in 224 (63.27%) cases and secondary dengue infection was detected in 130 (36.73%) cases. Conclusions: All suspected cases must be monitored for all three parameters i.e. NS1 Ag, IgM and IgG antibodies to differentiate between primary and secondary infection. Discrimination between primary and secondary dengue infections is important as the possibility of DHF and DSS is more in secondary infection.